Overcoming Illiteracy in Women and Girls. Issue 2 (March 2019) - Callister, Lynn Clark
Abstract : Literacy is directly linked to health outcomes. Our global health and nursing expert, Dr. Callister, discusses various programs in the United States and around the world that are working to promote literacy.